Design and Build a Water Level Monitoring System in IoT-Based Reservoirs - Mohammad Hufait Ibri Al Fahhiz; Sujono Sujono (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Water is a natural resource that has a crucial role for the lives of all creatures, including humans. In modern life, the use of water reservoirs is a common solution to store water to meet the needs of households, industries, and public facilities. One of the main challenges in managing water reservoirs is ensuring that the availability of water in reservoirs remains optimal. In traditional systems, water level monitoring is usually done manually using visual methods or simple buoys. However, this method has several drawbacks, such as the risk of human error, for example errors in reading water levels or negligence in conducting routine monitoring. Although automatic buoys are now available, this tool still has some drawbacks, such as limitations in obtaining real-time data and access to information that can only be done at the reservoir location, so monitoring still requires more time and effort. This research aims to ensure that the availability of water in the reservoir remains optimal and increase efficiency in monitoring the reservoir. With this system, users can obtain real-time data on the water level in the reservoir, either through electronic devices directly or through integration with Internet of Things (IoT) technology. The system has been connected to the Telegram-based IoT platform, thus enabling practical remote monitoring and control through the Telegram app on the user's device. This makes it easier for users to monitor without having to be at the reservoir location. The system is also equipped with an automation feature, which allows automatic control of the water pump based on the water level detected by the sensor. When the water in the reservoir is below the minimum limit, the system will automatically activate the pump to fill the water. On the other hand, if the water reaches the maximum limit, the pump will be turned off automatically to prevent overflow and avoid waste. In addition, the system also supports manual control through the Telegram platform, where users can turn the pump on or off remotely by simply sending a command through the Telegram app. The test results show that this system works accurately and efficiently in monitoring and controlling water, either automatically based on the water level detected by the sensor, or manually through commands sent through the Telegram application. With the application of IoT technology, this system is expected to improve the efficiency of water reservoir management, reduce human error, and support sustainability initiatives in the use of water resources.